The safety and efficacy of hybrid ablation for the treatment of atrial fibrillation: A meta-analysis - Jiang, Yun-Qiu (PLoS One, 2018)
INTRODUCTION: Hybrid ablation, an emerging therapy that combines surgical intervention and catheter ablation, has become a viable option for the treatment of persistent atrial fibrillation. In this analysis, we aimed to evaluate the safety and efficacy of hybrid ablation, as well as compare the outcomes of one-step and staged approaches. METHODS: We conducted a search in major online databases and selected the studies that met the inclusion criteria. The primary endpoint was defined as no episode of atrial fibrillation or atrial tachycardia lasting longer than 30 seconds without administration of antiarrhythmic drugs. RESULTS: Sixteen studies including 785 patients (paroxysmal atrial fibrillation, n = 83; persistent atrial fibrillation, n = 214; long-standing persistent atrial fibrillation, n = 488) were selected. Average history of atrial fibrillation was (5.0±1.6) years. The pooled proportion of patients who were arrhythmia-free at the primary endpoint was 73% (95% CI, 64%–81%, Cochran’s Q, P<0.001; I(2) = 81%). The pooled rate of severe short-term complications was 4% (95% CI, 2%–7%, Cochran’s Q, P = 0.01; I(2) = 51%). The success rate after one-step procedures (69%) was lower than that after staged procedures (78%). The staged approach could ultimately prove to be safer, although complication rates were relatively low for both approaches (2% and 5%, respectively). CONCLUSIONS: Hybrid ablation is an effective and generally safe procedure. The current data suggest that staged hybrid ablation could be the optimal approach, as it is associated with a higher success rate and a seemingly lower complication rate. Additional randomized controlled trials are necessary to confirm these results.